Serum Biochemistry Profile, Haematological Indices and Body Weight Gain of Albino Rats Fed Cookies Produced from Wheat (Triticum spp), Supplemented with Soyabeans (Glycine max) and Pro-vitamin A Cassava (Manihot utilisima crants) Flour Blends (Global Journal of Medical Research, 2020)
In this study, the serum biochemical, haematological indices and body weight gain of albino rats fed cookies produced from, supplemented with soya beans and pro-vitamin A cassava flour blends were determined, A preliminary work was carried out to ascertain the optimal acceptable level of soybeans using 0 to 20% (w/w) addition to wheat flour cookies production. Soybeans yielded the most acceptable cookies at 10% (w/w). Consequently in the main study, the level of soybean was maintained at 10% (w/w) while wheat and pro-vitamin A cassava were varied in the ratios of 100:0:0, 80:10:10, 70:10:20 and 60:10:30 giving a total of four samples. The cookies produced by standard methods were fed to 20 albino rats for thirty (30) weeks and were characterized for serum biochemistry profile, haematological indices and bodyweight gain using standard analytical methods.
Keywords: cookies; haematological; biochemistry and weight